DECOLONIALITY AND TEACHER TRAINING: LINKS FOR QUILOMBOLA SCHOOL EDUCATION - Márcio de Siqueira , Kárpio; Maria Vieira Lima Barbosa , Mônica; Gomes Soares , Edjane (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the relationship between decoloniality and teacher training in Quilombola School Education, seeking to reflect on how pedagogical practices based on this perspective can value and reconstitute the knowledge, cultural practices and identities of these communities. The research, with a qualitative approach, used interpretative analysis of official documents, specialized literature and research, aiming to understand the connections between traditional knowledge and pedagogical practices. The results indicate that the incorporation of decolonial approaches enriches resistance pedagogy, recognizes ancestral knowledge and contributes to a more inclusive and emancipatory education. It is concluded that decoloniality is fundamental to promoting pedagogical practices that are respectful of cultural and identity diversities, strengthening intercultural education that is resistant to epistemological colonialism. It is therefore suggested that there is a need for public policies that encourage this training among quilombola communities.  The research reinforces the importance of incorporating decolonial principles into teacher training to strengthen quilombola education in Brazil.